Editorial - Chakraborty, Rhyddhi (Bangladesh Journal of Bioethics, 2020)
Public health system always requires an advanced level of awareness and a comprehensive policy. However, as is often the case, expectations and actualities do not match. In order to understand the situation, planning and other related initiatives, and to assess the adequacy in terms of the expectations borne out of experiences, the papers in this volume detailed the issues and the need of ethics in formulating the policies and contributing in the vision of the development of the country. In order to have a comprehensive ethical policy and planning, a concern for the initiatives and development deep down in the policy formation is required. Despite the fact that there is need of ethics in such formulation, the need is yet to be acknowledged in the relevant policy documents. The five papers in the volume emphasise such need.